2015
DOI: 10.1016/j.obhdp.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

When beauty helps and when it hurts: An organizational context model of attractiveness discrimination in selection decisions

Abstract: a b s t r a c tWe propose and test a theory explaining how and why decision makers engage in attractiveness discrimination in selection decisions. We integrate status generalization with interdependence theories and contextualize attractiveness discrimination within interdependent relationships among decision makers and candidates. Drawing on status generalization theory, we propose that decision makers associate attractiveness with competence in male but not in female candidates. We then draw on interdependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 67 publications
2
38
0
3
Order By: Relevance
“…While these theoretical perspectives suggest more favorable perception and treatment of attractive people in general, attractiveness has been shown to lead to more unfavorable perception and responses in certain situations. As we noted in the introduction, there are a few studies that found that attractive people are perceived and treated more negatively than unattractive people (Johnson et al, 2010;S. Lee et al, 2015; see also Agthe, Spörrle, & Maner, 2010;Agthe, Spörrle, & Maner, 2011;Luxen & Van De Vijver, 2006).…”
Section: Specific Goals May Override Pro-attractiveness Biasmentioning
confidence: 94%
See 2 more Smart Citations
“…While these theoretical perspectives suggest more favorable perception and treatment of attractive people in general, attractiveness has been shown to lead to more unfavorable perception and responses in certain situations. As we noted in the introduction, there are a few studies that found that attractive people are perceived and treated more negatively than unattractive people (Johnson et al, 2010;S. Lee et al, 2015; see also Agthe, Spörrle, & Maner, 2010;Agthe, Spörrle, & Maner, 2011;Luxen & Van De Vijver, 2006).…”
Section: Specific Goals May Override Pro-attractiveness Biasmentioning
confidence: 94%
“…However, a handful of recent studies suggest that such a conclusion overlooks complexity in the social perception of attractiveness and subsequent treatment based on those perceptions, with important consequences. For example, physically attractive females are sometimes discriminated against in selection for jobs that are stereotypically masculine (Johnson, Podratz, Dipboye, & Gibbons, 2010), and physically attractive men are discriminated against by decision-makers who fear being outperformed by good-looking coworkers (S. Lee, Pitesa, Pillutla, & Thau, 2015).…”
Section: Perceived Entitlement Causes Discrimination Against Attractimentioning
confidence: 99%
See 1 more Smart Citation
“…No contexto atual, ter um corpo magro é estar nos padrões sociais de beleza (CAVICHIOLI; ABOURIHAN; PASSONI, 2012) o que pode justificar tal dado. Além disso, Lee et al (2015) demonstrou que estar fora dos padrões sociais de beleza pode gerar discriminação em processos seletivos de empregos, o reforça a "necessidade" de obter resultados rápidos e satisfatórios com dietas e exercício físico. Para isso, muitas pessoas recorrem ao uso de medicamentos e/ou suplementos (MAIOLI, 2012).…”
Section: Discussionunclassified
“…Therefore, females compete with one another in domains of physical attractiveness, promoting and enhancing features that males find attractive (Cashdan, 1998;Schmitt & Buss, 1996). In support, attractive females are considered a threat to other females (Lee et al, 2015). This may act as an explanation for female use of makeup (Vaillancourt, 2013;Etcoff, 1999), as it is used to emphasise features deemed attractive by males.…”
mentioning
confidence: 99%